Secondary Postpartum Haemorrhage: Causes and Management In A Tertiary Care Hospital - Shazia Jabbar; Shakira Perveen; Raveesha Kumari (KARACHI MEDICAL AND DENTAL COLLEGE, 2019)
Objective: To find out the frequency of secondary  postpartum  haemorrhage  (pph)  as  well  as  its  causes and management in women presenting in a tertiary care hospital Methods: It was a descriptive case series study conducted  from  1st  January  2016  to  31st  December 2016 at the Department of Gynaecology and Obstetrics, Dr. Ruth K.M.Pfau Civil Hospital, Karachi.   All     the patients presenting with secondary postpartum haemorrhage in the specified  time  period  were  included in the study. The patient's age, parity, booking status,  mode  of  delivery,  place  of  delivery,  cause of secondary postpartum haemorrhage and management done was noted on a predesigned proforma. Results:  The average age of the women was 30.62 ± 4.37 years. Postpartum haemorrhage was ob- served in 130 patients, out of these 27 patients had secondary postpartum haemorrhage  with  a  fre- quency of 20.67%. Majority of the women with secondary pph were multiparous 17 (62.96%) with 21 (77.77%) being delivered vaginally compared to 6 (22.22%) who had caesarean section. Most of the women 16 (59.25%) presented with secondary pph around 10-14 days post-delivery. Retained placen-       tal pieces was identified as the commonest cause in 19 (70.37%) women, antibiotics was given to all       the patients, evacuation done in 19 (70.37%)  cases,  2  (7.40%)  women  had  obstetrical  hysterectomy and 1 (3.70%) woman had repair of uterus while 5 (18.51%) cases were managed conservatively. No maternal death was recorded. Conclusion: Secondary postpartum haemorrhage though less common but  is  found  to  be  associated with significant maternal morbidity which  require  timely  diagnosis  and  management  so  as  to  prevent life threatening complications.